Role of legitimacy in the relationships between water users and governance bodies under conditions of increasing water stress - Gearey, Mary (Cranfield University, 2005)
Water stress is an issue of increasing concern in developed countries. In particular localised water stress 'hot spots', are a new challenge. This emergence creates a series of difficulties. Firstly, the potential impact of water stress in modern political economies is not fully understood by either natural or social scientists. Secondly, policies targeted to limit water stress may need to be deployed well before it moves from an episodic to an endemic phenomenon. These policies may entail radical changes to the way water is valued and consumed by society. Understanding how existing relationships between water users and water governance bodies are negotiated is crucial to successful policy implementation. As water stress might potentially strain these relationships, the aim of this thesis is twofold. Firstly to determine where opportunities may exist for developing consensual, pro-resource strategies within and between these two stakeholder groups. Secondly, to examine the current strengths and weaknesses within these relationships to isolate what changes may need to be instigated in order to support approaches which manage water stress. Exploring the role that legitimacy plays in these current relationships will underpin this analysis. Legitimacy can be understood as the concept that explains how authority operates in modern political economies. In other words, legitimacy enables people, processes and policies to function; transaction costs are subsequently lower in polities where legitimacy is well embedded. Reflexively moving between theory and empirical fieldwork, a detailed analysis of one river catchment, the River Nene, and the water users and governance bodies within it, is undertaken. Primary conclusions suggest that water stress as a concept has a very low profile; however, different symptoms of water stress are recognised along the catchment with a wide range of possible solutions offered by stakeholders. Legitimacy is embedded within governance bodies along the catchment, though it is not uniformly distributed; this colours the perception of their effectiveness in water resource management. Novel policy options to ameliorate water stress are acceptable to water users, though reuse technologies and steep price hikes are rejected.